Pemanfaatan Learning Management System (LMS) dalam Meningkatkan Efektivitas Pembelajaran di Sekolah Menengah - Sahbuki Ritonga; Yuli Yani; Dwina Putri; Siti Aminah Hasibuan; Ali Sadikin Ritonga (Insan Zenius Ilmiah, 2026)
The development of information and communication technology encourages the education sector to adapt through the use of digital learning technology. One of the developing innovations is the use of Learning Management System (LMS) in the learning process at secondary schools. This research aims to describe the utilisation of LMS in enhancing the effectiveness of learning. The method used is a qualitative descriptive approach with teachers and students as research subjects. Data collection techniques include observation, interviews, and documentation. The research results show that the use of LMS can significantly enhance the effectiveness of learning. This is marked by increased student participation in learning activities, the development of learning independence, and the ease for teachers in managing materials, assignments, and learning evaluations. LMS also supports the creation of more flexible, structured, and interactive learning because it can be accessed anytime and anywhere. However, the utilisation of LMS still faces several obstacles, such as limited technological infrastructure and differences in digital literacy levels between teachers and students. Therefore, adequate support in terms of facilities and infrastructure, as well as the enhancement of digital competencies, is necessary so that the implementation of LMS can run optimally, effectively, and sustainably in improving the quality of learning in secondary schools.